The training of academics as a factor of barriers to teaching: an exploratory study in engineering - Oliveira, Lucas Duarte (2023)
In the transition from High School to Higher Education, not all students have a minimally satisfactory academic education that allows them to understand the subjects that are treated with in disciplines such as Differential and Integral Calculus I and Physics I. In this context, the main objective of the present is to point out possible intervention alternatives that may favor the learning of the mathematical contents foreseen in the disciplines of the initial semesters in Engineering courses. To this end, the analysis of a set of responses designed from two surveys applied is presented, respectively, to 101 students enrolled in Differential and Integral Calculus I of the Engineering courses at an institution of the Federal Education, Science and Technology Network, in the Midwest Region of Brazil and five professors who work with the teaching of mathematics at the same institution. The low percentage of correct answers by students in a test of elementary mathematical knowledge corroborates, to a large extent, the concerns signaled by the results of the questionnaires applied to the professors in relation to the students' lack of education. The alarming problem found requires countermeasures, as suggested in this work, mainly due to the possible negative effects of the Covid-19 pandemic on the worsening the training gaps of those entering undergraduate education.